WHAT DO YOU THINK YOU ARE? : The Science of What Makes You You - Clegg, Brian (London : Icon Books Ltd, 2021)
Popular science master Brian Clegg's new book is an entertaining tour through the science of what makes you, you. From the atomic level, through life and energy to genetics and personality, it explores how the billions of particles which make up you - your DNA, your skin, your memories - have come to be. It starts with the present-day reader and follows a number of trails to discover their origins: how the atoms in your body were created and how they got to you in space and time, the sources of things you consume, how the living cells of your body developed, where your massive brain and consciousness originated, how human beings evolved and, ultimately, what your personal genetic history reveals.
Includes index
Keywords: Human physiology -- Popular works; Human anatomy -- Popular works; Human body -- Popular works; Popular works